Osteomyelitis of the knee following intra-articular injections: a case series - Devnani, Anand Sobhraj; Yeak, Raymond Dieu Kiat; Che Hamzah, Fahrudin (Nepal Medical Association, 2020)
Septic arthritis of the knee is rare in adults. This leads to difficulty in making early diagnosis that invariably leads to delayed treatment with consequent destruction of the joint. The delay in diagnosis is largely attributed to absence of clinical signs of flagrant infection. Reported are three adult patients who presented with painful swollen knee and inability to walk few weeks after intra-articular injection for osteoarthritis. This paper discusses the cases in which the difficulties in the early diagnosis of septic arthritis of knee in adults led to the development of osteomyelitis.